Dinamika Pembentukan Karakter Melalui Kegiatan Mengaji Rutin - M.arif rohman mauzen; Zainal arifin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Character has a significant role in shaping quality individuals and making a positive contribution to society. Education is recognized as an effective means of character development, and one non-formal approach that has great potential is through regular recitation activities. This activity is periodically carried out to understand religious teachings and can be held in various places such as mosques, prayer rooms, or homes. Within the scope of the Sidotopo Dipo Gang 2 Kompleks in Surabaya, routine reciting activities are identified as key elements that shape the character of citizens. Its positive impact involves increasing religious understanding, strengthening moral values, bonding social relations, and increasing social awareness. This research applies a qualitative approach with an in-depth case study method in the Sidotopo Dipo Gang 2 Kompleks. The subjects of the study consisted of citizens who were active in routine reciting activities. Data were collected through interviews, observations, and documentation, then analyzed qualitatively to provide an overview of the dynamics of character building of citizens through routine recitation activities.